Analisis Faktor Rendahnya Minat Baca Siswa Kelas III Mata Pelajaran Bahasa Indonesia SD Negeri 3 Sidorejo - Asriyanti, Frita Devi; Alfito, Muhammad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to find out what factors cause low interest in reading in class III students at SDN 3 Sidorejo. This type of research is qualitative research with a descriptive approach. The research subjects were class students, teachers and parents. Data collection techniques in this research used observation, interviews and documentation. The data analysis technique in this research uses data reduction, data presentation, and drawing conclusions or verification. Checking the validity of this research data uses triangulation techniques. The results of this research are factors that influence the low interest in reading in class III students at SD Negeri 3 Sidorejo, including: students' feelings of enjoyment towards reading, attention and awareness within students in reading activities. Motivation for reading from teachers in getting used to reading books in learning Indonesian makes students interested and enjoy reading books. Teachers become creators, facilitators and evaluaters in increasing students' reading interest. The literacy environment in the classroom influences students' interest in reading. Reading facilities really support students' reading, such as reading books, libraries and comfortable reading areas.